Annular injuries following the insertion of heart valve prostheses. Issue 5 (September 1974) - Bowes, Vernon F.; Datta, Bhoopendra N.; Silver, Malcolm D.; Minielly, John A.
Abstract : Bowes, V. F., Datta, B. N., Silver, M. D. and Minielly, J. A. (1974). Thorax, 29, 530-533. Annular injuries following the insertion of heart valve prostheses. The clinical presentation and morphological findings in eight cases of annular injury associated with the insertion of prosthetic heart valves are discussed. The lesions presented as a separation of the left atrium and ventricle at the mitral annulus (one patient), a sinus or false aneurysm in the left posterior atrioventricular groove (two patients), or as a separation of the aortic root from the base of the heart (five patients). The pathogenesis of the lesions is similar. Annular tissue was weakened either by the removal of excess tissue or by an abnormal stress placed on normal tissue or by a slight stress placed on tissue altered by disease, and, as a result, it separated or tore. The resultant haemorrhage either caused the patient's death or, with time, produced the other morphological findings. Factors predisposing patients to the injuries are discussed and a differential diagnosis of annular pseudoaneurysms is provided.